Complete Pass-Through in Levels - Kunal Sangani (The Quarterly Journal of Economics, 2026)
Abstract Empirical studies find that the pass-through of input cost changes to prices is incomplete: a 10% increase in costs causes downstream prices to rise less than 10%, even at long horizons. Using microdata from gas stations, food products, and manufacturing industries, I find that incomplete pass-through in percentages often disguises complete pass-through in levels: a $1/unit increase in input costs leads to $1/unit higher downstream prices. Pass-through appears incomplete in percentages due to a gap between prices and costs. Complete pass-through in levels contrasts with workhorse macroeconomic models that feature homothetic industry demand systems. I identify an alternative class of demand systems that yields pass-through in levels and highlight four implications. First, measuring pass-through in percentages can lead to spurious evidence of asymmetry and size dependence. Second, pass-through in levels leads to systematic fluctuations in relative price and markup dispersion that are not associated with changes in allocative efficiency. Third, pass-through in levels can explain dynamics of industry gross margins, operating profits, and entry in the data that are at odds with workhorse models. Finally, incorporating pass-through in levels into an input-output model of the U.S. economy better matches the volatility of consumer price inflation and the response of inflation to identified shocks.